2022
DOI: 10.1007/s12560-022-09520-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Food Against Inactivation of Human Coronavirus OC43 by Gastrointestinal Fluids

Abstract: The involvement of the gastrointestinal (GI) tract in severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection has been reported in multiple studies. Since it has been demonstrated that human intestinal epithelial cells support productive viral replication and that a substantial portion of infected individuals shed the virus in feces, the possibility of fecal–oral and fecal-respiratory modes of transmission have been proposed for SARS-CoV-2. In order to establish viral replication in the intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Water is commonly present on the surface of raw plant materials. Furthermore, HCoV-OC43 can remain infectious in simulated gastrointestinal fluids during feeding, and food may increase its stability ( Harlow et al, 2022 ). In this study, water showed no or low antiviral activity against dried HCoV-OC43 compared with NEW.…”
Section: Resultsmentioning
confidence: 99%
“…Water is commonly present on the surface of raw plant materials. Furthermore, HCoV-OC43 can remain infectious in simulated gastrointestinal fluids during feeding, and food may increase its stability ( Harlow et al, 2022 ). In this study, water showed no or low antiviral activity against dried HCoV-OC43 compared with NEW.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study also demonstrated that the infectivity of SARS-CoV-2 and HCoV-229E was maintained in FaSSIF but lost in FeSSIF containing bile salt ( Lee et al, 2020 , Zhou et al, 2017 ). Other studies showed that HCoV-OC43 and MERS-CoV were resistant to FaSSIF and FeSSIF ( Harlow et al, 2022 , Zhou et al, 2017 ). In another study, residual SARS-CoV-2 mNeonGreen reporter virus was present after 1 h of treatment with simulated small intestinal fluid ( Zang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…HCoV-OC43 survived at all FeSSGF pHs as in this study. Additionally, the presence of food (cucumber) in FeSSGF significantly increased the survival of HCoV-OC43 ( Harlow et al, 2022 ). This study showed that HCoV-229E maintained its infectivity in FaSSIF (pH 7), whereas the virus was inactivated in FeSSIF (pH 5) containing pancreatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of infectious viral particles for HCoV‐OC43 was determined by TCID 50 using MRC‐5 cells as described previously (Harlow, et al 2022). A negative control consisting of MEM maintenance media and a positive control consisting of diluted HCoV‐OC43 stock, were also included.…”
Section: Methodsmentioning
confidence: 99%